Reproduction in the intertidal limpet Cellana ornata in southern New Zealand - R. A. Dunmore; D. R. Schiel (New Zealand Journal of Marine and Freshwater Research, 2000)
The reproductive cycle of the abundant intertidal limpet Cellana ornata (Dillwyn 1817) was examined over 19 months, covering two breeding periods, on a rocky intertidal platform in southern New Zealand. A gonad index was calculated, and histological sections were used to count the numbers of mature and immature eggs present. Fecundity was estimated using counts of eggs before and after spawning. To determine any variation between sites, the gonad index of limpets at a second site dominated by boulders was examined over 6 months during the second breeding period. C. ornata had a single spawning period annually during summer, with greatest gonad sizes in January‐February. There were significant differences in peak gonad indices between two breeding seasons on the platform. Within the second breeding period, both the timing and magnitude of peak gonad development differed between sites, with lower reproductive output at the boulder site. Fecundity increased with increasing size, but individuals are probably capable of reproducing after their first year on the shore. The life history of this species is discussed in comparison to other limpets in New Zealand.